The ECB is running out of policy space: can fiscal policy help? - Capolongo, Angela; Gros, Daniel (Economics and Business Letters, 2020)
The European Central Bank is running out of instruments for addressing persistent low inflation. In this paper, we assess if a fiscal policy expansion could help the ECB reaching its target. Using ten mainstream models, we find only a modest and temporary impact of a fiscal deficit of 1% of GDP on inflation.